Analysis of cryogenic tool wear during electrical discharge machining of titanium alloy grade 5. (2020) - Choudhary, Rajesh; Kumar, Amar; Yadav, Gyanendra; Yadav, Rammurat; Kumar, Vikas; Akhtar, Javed
Abstract: The extensive use of Titanium alloy Ti-6Al-4V in defense, aerospace, automotive and biomedical sectors has made this material most demandable among industries. Due to low thermal conductivity it is difficult to machine by conventional machining processes. Electric discharge machining is a viable option to machine extremely harder and electrically conductive materials. There are a lot of possibilities in EDM to machine super alloys. Electrical discharge machining has also huge potential when it comes to biomaterials. Super alloy like Titanium grades 5 is most suitable for the biomedical field due to its desirable bio-compatible properties. In this study effect of cryogenic treatment of tool, current, pulse on time, pulse off time and voltage has been investigated on tool wear rate. Optimized conditions for minimum tool wear rate have been found and microstructural analysis was also carried out to observe the surface topography of machined surface with non treated and cryogenic treated tool electrode. It has been observed that tool wear rate of cryogenic copper tool is comparatively more as compared to non treated copper tool electrode. The effect of current, on-time and type of tool electrode is found to be more pronounced as compared to other machining parameters. Thick recast layer with wide surface cracks is observed on the surface machined by the non treated tool electrode. Whereas narrow micro cracks with thin recast layer is observed on the surface machined by cryogenic treated tool electrode.